Uji In Vitro dan Studi In Silico Senyawa Turunan n’-benzoylisonicotinohydr - Ruswanto Ruswanto; Nur Rahayuningsih; Nur Laeli Dwi Hidayati; Ginna Sri Nuryani; Richa Mardianingrum (Fakultas Farmasi Universitas Pancasila, 2019)
There have been in silico and in vitro studies of N-Benzoylisonicotinohydrazide derivatives as antituberculosis candidates. The aims of this research were determined that the N'-benzoylisonicotinohydrazide derivatives could inhibit the activity of gram-positive, gram-negative and Mycobacterium tuberculosis, as well as having good interactions with Enoyl-Acyl Carrier Protein Reductase from Mycobacterium Tuberculosis. From the in vitro test it was found that the N'-benzoylisonicotinohydrazide compound had a Minimum Inhibitor Concentration (MIC) of 0.33 µg / ml against the Basillus subtilis, while the Minimum Inhibitor Concentration (MIC) of N '- (2-chlorobenzoyl) isonicotinohydrazide against Mycobacterium tuberculosis (H37Rv) was 3.125 µg / ml. From the in silico study, it was found that the binding affinity value between N '- (2-chlorobenzoyl) isonicotinohydrazide enzyme Enoyl-Acyl Carrier Protein Reductase (2X23) had the smallest binding affinity so that it could be predicted that it had a stable interaction than other compounds so that the N '- (2-chlorobenzoyl) isonicotinohydrazide could be used as a more potent antituberculosis candidate.